Patellar fracture among elite-level European soccer players: 4-year case-control cohort analysis of return to play, re-injury, and player performance - Patel, S.; Lavoie-Gagne, O.; Mehta, N.; Farah, G.; Korrapati, A.; Forsythe, B. (The Physician and Sportsmedicine, 2023)
Objectives There is a paucity of literature investigating the relationship between patellar fracture and player performance of professional soccer players following return to play (RTP). Our goal is to determine the rate of RTP, time to RTP, and effect on player performance following patellar fracture.